Concrete carbon mixing – A systematic review on the processes and their effects on the material performance - Marco Davolio; Giovanni Muciaccia; Liberato Ferrara (Cleaner Materials)
The need for concrete industry to meet the climate neutrality target raised the attention towards carbon capture and utilization (CCU) technologies. Among the various solutions, cementitious materials can benefit from enforced carbonation, a thermodynamically stable reaction that permanently sequesters carbon dioxide into cement compounds. A possible enforced carbonation process is concrete carbon mixing, which involves the addition of pumping systems into concrete production lines to inject carbon dioxide into the material while in a fresh state. Various studies attempted to improve the efficiency of the process and to increase the quantity of fixed carbon dioxide. The current literature was systematically analysed to provide an overview of process parameters, possible injection systems, and properties of carbonated cementitious products. The studies were classified according to the injection stage: carbonation of the mixing water, carbonation of the cement slurry, or injection during concrete mixing with all the components. Concrete carbon mixing has proven to be promising for carbon dioxide sequestration through enforced carbonation, as the injection process enhanced the properties of the final product in most instances. In addition, other relevant aspects of carbon dioxide sequestration processes were discussed. Firstly, the methods and formulations to determine the CO2 uptake were presented together with cross-comparison studies. Moreover, the methodological aspects of life cycle assessment (LCA) applied to concrete carbon mixing processes were discussed, showing the lack of systematic studies. In conclusion, simplified evaluations demonstrated the economic viability of carbon dioxide injection in fresh concrete, supporting future industrial deployment and discussing the challenges for the upscaling.